Current reclamation practices after oil and gas development do not speed up succession or plant community recovery in big sagebrush ecosystems in Wyoming. Issue 1 (16th July 2017) - Rottler, Caitlin M.; Burke, Ingrid C.; Palmquist, Kyle A.; Bradford, John B.; Lauenroth, William K.
Abstract: Reclamation is an application of treatment(s) following disturbance to promote succession and accelerate the return of target conditions. Previous studies have framed reclamation in the context of succession by studying its effectiveness in reestablishing late‐successional plant communities. Reestablishment of plant communities is especially important and challenging in drylands such as shrub steppe ecosystems where succession proceeds slowly. These ecosystems face threats from climate change, invasive species, altered fire regimes, and land‐use change, as well as fossil‐fuel extraction and associated disturbance. As such, the need for effective reclamation after this type of energy development is great. However, past research regarding this type of reclamation has focused on mining rather than oil and gas development. To better understand the effect of reclamation on rates of succession in dryland shrub steppe ecosystems, we sampled oil and gas wellpads and adjacent undisturbed big sagebrush plant communities in Wyoming, U.S.A., and quantified the extent of recovery for forbs, grasses, and shrubs on reclaimed and unreclaimed wellpads relative to undisturbed plant communities. Reclamation increased the recovery rate for early‐successional types, including combined forbs and grasses and perennial grasses, but did not affect recovery rate of late‐successional types, particularly big sagebrush and perennial forbs. Rather, subsequent analyses showed that recovery of late‐successional types was affected by soil texture and time since wellpad abandonment. This is consistent with studies in other ecosystems where reclamation has been implemented, suggesting that reclamation may not help reestablish late‐successional plant communities more quickly than they would reestablish naturally.